Variations in the line Нα of the Herbig Ae type star HD 179218 - H. N. Adigezalzade (Вісник Астрономічної школи, 2018)
Young stars in which subsoil processes of thermonuclear synthesis and which shine at the expense of the continuing gravitational compression haven't begun yet are one of the astrophysics objects which are most actively investigated today. It is caused by the fact that studying of the nature of the physical processes proceeding in circumstellar gas-and-dust disks, people around young stars, and, especially, in a boundary region between a surface of a star and a disk helps to shed light on such poorly studied problems of astrophysics as the nature of star magnetism, physical mechanisms of accretion and star wind, structure and dynamics of internal areas of accretionary disks and many others. As it is established now, the young stars which haven't come to the Main Sequence (MS) yet are surrounded with extended gas-and-dust covers. Radiation of their dust can find them as indirect methods on IK, and direct methods (the direct spatial images of objects received in IK, submillimetric, millimetric and radio frequency ranges). Substance of these covers is created from the remains of a parental gas-and-dust cloud. In the course of evolution the main part of a cover forms a protoplanetary disk in which then there is a process of formation of planets, and other part or accretes on a star, or dissipates (star wind). The research Ai/Ve of stars of Herbiga proceeding four decades has shown that they are very non-uniform on the photometric and spectral properties and, actually, can be divided into several groups. The results of spectral monitoring of the Herbig Ae/Be star MWC 614 (HD 179218) have presented. It was discovered two wavelike quasi-cyclic variations of parameters of the emission component of the line Нα with character time ∼40 days. The first of wavelike variability is more deep and is clear demonstrated a decrease and increase of spectral parameters of the line. The same time at the first minimum it was discovered unusual changes in profiles of the line Нα which are showed an appearance and disappearance of additional blue and red emission components. Obtained results are giving a reason of supposing on duplicity of the star. It was research the variability in time of equivalent widths and radial velocities and spectral line profiles, which are formed in different regions of the circumstellar environment of these stars. It is shown that the most active changes in the spectrum observed in the lines of hydrogen the Hα, Hβ and Hel 5876. The rest of the emission lines, e.g., Si II λλ6347, 6371ÅÅ, [O I] λλ6300, 6363ÅÅ also observed variability, but on a much smaller scale. For star MWC 614 for the first time found the band of interstellar origin DIB λλ5780 and 5797ÅÅ. It is shown that the active processes in the circumstellar environment can be distributed in a more remote part of the circumstellar disk.